2021
DOI: 10.1038/s41390-021-01422-9
|View full text |Cite
|
Sign up to set email alerts
|

Catch-up growth in juvenile rats, fat expansion, and dysregulation of visceral adipose tissue

Abstract: A prime concern of young patients with Polycystic Ovary Syndrome (PCOS) is the control of body adiposity, given their tendency to gain weight and/or their difficulty to lose weight. Circulating growth-and-differentiation factor-15 (GDF15) facilitates the control of body weight via receptors in the brainstem. C-reactive protein (CRP) and insulin are endogenous GDF15 secretagogues. We hypothesised that PCOS in non-obese adolescents is characterised by low concentrations of circulating GDF15, when judged by the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In addition to the classical axis formed by ACE, accumulating evidence has revealed a new axis, implicating ACE type 2 (ACE2). ACE produces several peptides such as Ang- (1)(2)(3)(4)(5)(6)(7)(8)(9), derived from Ang I, alamandine, derived from Ang A and Ang 1(1-7), derived from Ang II or from Ang- (1)(2)(3)(4)(5)(6)(7)(8)(9), the latter through the enzymatic activity of ACE or neutral endopeptidase (NEP). In turn, Ang-(1-7) can interact with MasR and Alamandine with MrgD receptors, exerting vasorelaxant, antiproliferative and antifibrotic actions [14], but also exerting a pivotal role in balancing the vasoconstrictor, proliferative and fibrotic actions of Ang II through AT1 receptors [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the classical axis formed by ACE, accumulating evidence has revealed a new axis, implicating ACE type 2 (ACE2). ACE produces several peptides such as Ang- (1)(2)(3)(4)(5)(6)(7)(8)(9), derived from Ang I, alamandine, derived from Ang A and Ang 1(1-7), derived from Ang II or from Ang- (1)(2)(3)(4)(5)(6)(7)(8)(9), the latter through the enzymatic activity of ACE or neutral endopeptidase (NEP). In turn, Ang-(1-7) can interact with MasR and Alamandine with MrgD receptors, exerting vasorelaxant, antiproliferative and antifibrotic actions [14], but also exerting a pivotal role in balancing the vasoconstrictor, proliferative and fibrotic actions of Ang II through AT1 receptors [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in LBW children have demonstrated that catch-up growth increases the risk of developing cardio-metabolic diseases later in life [ 5 , 6 , 7 ]. In experimental animal models, there is also evidence that catch-up growth during lactation has deleterious consequences, leading to adipose tissue accumulation [ 8 , 9 ]. In a rat model of fetal programming induced by undernutrition (MUN rat), we have observed that catch-up growth also affects cardiovascular organs; male rats exposed to undernutrition are born with a smaller aorta, which is enlarged during lactation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present study demonstrated that F2_D rats showed abnormal body weight in adulthood. Regardless of whether the newborn is classified as small (SGA) or large (LGA) for gestational age, consequences occur in adult life due to abnormal growth to compensate for the birth weight [ 19 ]. Sinzato et al [ 11 ] showed that female F2_D rats were born SGA.…”
Section: Discussionmentioning
confidence: 99%
“…The short-term benefits of rapid and accelerated growth are resistance to infections and childhood survival [ 21 ]. However, intrauterine restriction-induced catch-up growth in rats increases the adipocyte size in the retroperitoneal muscle, which increases the levels of circulating triglycerides and HOMA-IR, indicating the effect of catch-up growth on fat accumulation and abnormal metabolism [ 19 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…the NN-Veh, NN-TU, UN-RG-Veh, and UN-RG-TU groups, but not a NN-RG-Veh or NN-RG-TU group because of the restrictions of our animal facility accommodation. It is noted that Lizarraga-Mollinedo reported that different growth speed in the pups with undernourishment in utero showed conflicting levels of gene expression patterns in adipose tissue compared to normally nourished pups by using rat animal model ( 44 ). We did not investigate a condition without HFD due to the same animal facility limitation.…”
Section: Discussionmentioning
confidence: 99%